Change proof : leveraging the power of uncertainty to build long-term resilience - Markel, Adam (McGraw Hill-Ascent Audio, 2022)
In his #1 bestselling guide to resilience, Pivot, business and personal development expert Adam Markel showed how building resilience can supercharge your life and career. Now, in Change Proof, he shows how you can move beyond managing change to actively embracing it-and actually using times of uncertainty, crisis, and chaos to create opportunities and stimulate positive growth. Broken down into four parts, Change Proof explores the dynamics of change and provides a model of how to create the mindset that embraces it fully. Using case studies, current research, and his years of experience as an expert in the integration of business and personal development, Markel uses real-life scenarios to illuminate the lessons in engaging chapters that include: The Myth of Balance; The Resilience Bank Account; Recovery vs. Burnout; Even Michael Jordan Paused; Get Out of Your Head; A Little Failure Goes a Long Way; Calm Is Contagious; and What Change-Proof Culture Can Do for You. You'll learn how to choose change before it chooses you, what it takes (and what it means) to become truly change proof, and how to leverage your relationship to change. Change Proof will help you take the art and science of resilience to the next level-and look forward to future and all the changes it will bring, with full confidence.